Rogues and regulation in global finance: Maxwell, Leeson and the City of London - Clark, G (Routledge, 1997)
In this paper, I explore the culture of the finance industry in general and, in particular, the problems of dealing with socalled rogue behaviour in the context of regulation and regulatory regimes. The reference points for analysis are the recent cases of Robert Maxwell, the British entrepreneur who is thought by many to have systematically 'fleeced' his companies' pension funds to finance complex corporate deals, and Nick Leeson, the Barings trader (in Singapore) who, it is commonly believed, single-handedly bankrupted the bank. While no doubt provocative and the subjects of considerable speculation regarding their true motives, I argue that the Maxwell and Leeson cases are representative of a strategy of demonization and selective representation designed to protect the reputations of existing institutions. In this respect, I focus upon three issues: the representation of behaviour; the significance of an industry's culture for individual behaviour; and the scope of regulation. The paper includes a discussion of the flawed logic of explanations of individual behaviour that do not take seriously the context of behaviour. To illustrate, I begin with Mrs Maxwell's recent biography of her late husband and then concentrate on recent government reports and commentaries related to Leeson and the Barings' collapse. The paper concludes with an analysis of these issues with reference to the global regulation of the securities industry.